2021
DOI: 10.1002/jcv2.12034
|View full text |Cite
|
Sign up to set email alerts
|

Prediction models for child and adolescent mental health: A systematic review of methodology and reporting in recent research

Abstract: Background There has been a rapid growth in the publication of new prediction models relevant to child and adolescent mental health. However, before their implementation into clinical services, it is necessary to appraise the quality of their methods and reporting. We conducted a systematic review of new prediction models in child and adolescent mental health, and examined their development and validation. Method We searched five databases for studies developing or validating multivariable prediction models fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 56 publications
0
22
0
Order By: Relevance
“…Future research may also look at the use of the identified early markers and precursors to develop a prediction model for later ADHD. However, the use of prediction models within child and adolescent psychiatry has been shown to have limited utility, in part due to methodological issues such as sample size and replicability, which would have been seen in this study had we developed such a model (Larsson, 2021;Senior et al, 2021).…”
Section: Methodological Strengths and Limitationsmentioning
confidence: 96%
“…Future research may also look at the use of the identified early markers and precursors to develop a prediction model for later ADHD. However, the use of prediction models within child and adolescent psychiatry has been shown to have limited utility, in part due to methodological issues such as sample size and replicability, which would have been seen in this study had we developed such a model (Larsson, 2021;Senior et al, 2021).…”
Section: Methodological Strengths and Limitationsmentioning
confidence: 96%
“…Although beyond the scope of the present paper, the work by Tobarra-Sanchez et al also (2022) emphasizes the need for the field to go beyond individual predictors and begin to develop and test prognostic diagnostic models (Larsson, 2021;Senior et al, 2021) which have direct translational implications. For example, prognostic…”
Section: Adhd Early Identification Predictionmentioning
confidence: 93%
“…One of the most striking findings reported by Senior et al (2021) is that only 2 of the 100 eligible studies demonstrated a low 'risk of bias', driven both by inappropriate analytic strategies and insufficient reporting of key study characteristics. Risk of bias was evaluated across four domains (participants, predictors, outcome and analysis) using the Prediction model Risk Of Bias ASsessment Tool (PROBAST; Wolff et al, 2019).…”
Section: Analytic Qualitymentioning
confidence: 99%